Autistic Ethos at Work: Writing on the Spectrum in Contexts of Professional and Technical Communication - Shannon Walters (Disability Studies Quarterly, 2011)
I explore the rise of international technology companies that recruit people with autism and Asperger's Syndrome, focusing specifically on the type of professional ethos that these companies cultivate for their employees. Using theories of ethos and communication from the field of technical communication, I argue that these companies often predetermine a limited sense of professional ethos for employees and reinforce stereotypes about people with autism. More broadly, I examine how this limitation is indicative of the ableism of traditional formulations of ethos in the rhetorical tradition. I then turn to potential revisions that technical communicators with autism can offer. Specifically, I examine two technical and professional writers in particular—Temple Grandin and Dawn Prince Hughes—showing how each invents a professional ethos that resists stereotypes about autism and what it means to be an "ideal" professional communicator.
Keywords: Autism; Technical and Professional Communication; Ethos